2020
DOI: 10.1001/jamanetworkopen.2020.2034
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Analysis of the Elder-Friendly Approaches to the Surgical Environment (EASE) Intervention for Emergency Abdominal Surgical Care of Adults Aged 65 Years and Older

Abstract: IMPORTANCE The Elder-Friendly Approaches to the Surgical Environment (EASE) initiative is a novel approach to acute surgical care for elderly patients. OBJECTIVE To determine the cost-effectiveness of EASE. DESIGN, SETTING, AND PARTICIPANTS An economic evaluation from the perspective of the health care system was conducted as part of the controlled before-and-after EASE study at 2 tertiary care centers, the University of Alberta Hospital and Foothills Medical Centre. Participants included elderly adults (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Another recent study using a proactive approach for patients over 65 years presenting for emergency general surgery with integration of a geriatric assessment team, optimization of evidence-based elder-friendly practices, promotion of patient-oriented rehabilitation, and early discharge planning found a significant reduction in mortality, length of stay and discharge to a higher level of care [ 95 ]. Proactive management of these frail patients may also decrease the costs of care [ 97 , 98 ]. At present the evidence indicates that most older emergency laparotomy patients are not reliably assessed for frailty nor co-managed with a care of the elderly team [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study using a proactive approach for patients over 65 years presenting for emergency general surgery with integration of a geriatric assessment team, optimization of evidence-based elder-friendly practices, promotion of patient-oriented rehabilitation, and early discharge planning found a significant reduction in mortality, length of stay and discharge to a higher level of care [ 95 ]. Proactive management of these frail patients may also decrease the costs of care [ 97 , 98 ]. At present the evidence indicates that most older emergency laparotomy patients are not reliably assessed for frailty nor co-managed with a care of the elderly team [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patient satisfaction at six weeks remained high at the intervention site, and significantly improved Pre-EASE to Post-EASE at the control site. In combination with the EASE interventions demonstrating the clinical and economic benefits, the stable QOL outcomes and patient satisfaction provides further support for elder-friendly surgical care [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Elder-friendly Approaches to the Surgical Environment (EASE) study was one of the largest studies conducted to assess the benefit of an ACE-style model of care in an emergency general surgical population. The EASE study demonstrated improved clinical and economic benefit [ 22 , 23 ]. Recognizing that surgery has significant implications for patients’ nutrition and QOL, as a secondary outcome of the EASE study, we assessed post-discharge patient reported outcomes with the hypothesis that this integrated care will confer a benefit for QOL and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…27 These findings have informed quality improvement efforts in other vulnerable emergency surgical patients including general surgery, 28,29 emergency laparotomy 2,30 and vascular surgery. 31 Collaborative care models have shown better care coordination, 29,31 decreased complications including delirium and functional decline, 31,32 shorter hospital stays 31,32 and potential cost savings 33 . Observational data from the National Emergency Laparotomy Audit (NELA) in the United Kingdom (UK) show that postoperative geriatrician review is associated with lower mortality in older emergency laparotomy patients, 34,35 while meta-analyses of studies of co-management of surgical patients by geriatricians 36 or general physicians 37 suggest that mortality benefits accrue in models including a multidisciplinary team in addition to the medical specialist.…”
Section: Evidence For Collaborative Perioperative Care Of Older Peoplementioning
confidence: 99%
“…And finally, there is the important practical challenge of resourcing, including availability of a skilled medical and multidisciplinary workforce, and financial remuneration and costs of establishing a perioperative medicine service within surgery. The evidence to support the cost saving of co‐management models is mixed, 33,46 but it is hard to measure cost savings of the harm that never happened from a procedure that never occurred. Health services receive funding based on activity, 51 but teamwork, collaboration and long‐term patient outcomes have rarely been incentivized.…”
Section: Why Is Team‐based Perioperative Care So Challenging?mentioning
confidence: 99%